Chronic liver inflammation and hepatocellular carcinogenesis are independent of S100A9. Issue 10 (13th November 2014) - De Ponti, Aurora; Wiechert, Lars; Stojanovic, Ana; Longerich, Thomas; Marhenke, Silke; Hogg, Nancy; Vogel, Arndt; Cerwenka, Adelheid; Schirmacher, Peter; Hess, Jochen; Angel, Peter
<x xml:space="preserve">Abstract</x> The S100A8/A9 heterodimer (calprotectin) acts as a danger signal when secreted into the extracellular space during inflammation and tissue damage. It promotes proinflammatory responses and drives tumor development in different models of inflammation‐driven carcinogenesis. S100A8/A9 is strongly expressed in several human tumors, including hepatocellular carcinoma (HCC). Apart from this evidence, the role of calprotectin in hepatocyte transformation and tumor microenvironment is still unknown. The aim of this study was to define the function of S100A8/A9 in inflammation‐driven HCC. Mice lacking S100a9 were crossed with the Mdr2−/− model, a prototype of inflammation‐induced HCC formation. S100a9−/− Mdr2−/− (dKO) mice displayed no significant differences in tumor incidence or multiplicity compared to Mdr2−/− animals. Chronic liver inflammation, fibrosis and oval cell activation were not affected upon S100a9 deletion. Our data demonstrate that, although highly upregulated, calprotectin is dispensable in the onset and development of HCC, and in the maintenance of liver inflammation.